Dichotomization of the new revised international prognostic scoring system for a better clinical stratification of patients with myelodysplastic syndromes. Issue 6 (12th May 2019) - Montoro, Julia; Pomares, Helena; Villacampa, Guillermo; Merchán, Brayan; Molero, Antonieta; Alonso, Esther; Gallur, Laura; Grau, Javier; Salamero, Olga; Roldán, Elisa; Saumell, Silvia; Ortega, Margarita; et al.
Abstract: In clinical practice, patients with myelodysplastic syndromes (MDS) are usually classified in low or high-risk groups to take therapeutic decisions, conservative for low-risk, whereas active for high-risk. Nevertheless, in the Revised International Prognostic Scoring System (IPSS-R) is not well stated which patients are low or high-risk. This study was aimed to ascertain in 364 MDS patients which IPSS-R threshold better dichotomized in low vs. high-risk. The best dichotomization was obtained with an IPSS-R cut-point of 3. Accordingly, 68% patients were classified as low-risk (median OS, 61.3 months) and 32% as high-risk MDS (median OS, 13.9 months) ( p < .001). Interestingly, the intermediate IPSS-R risk patients presented an OS more related to the high IPSS-R than to the low IPSS-R risk group. In conclusion, an IPSS-R cut-point of 3 led to a meaningful stratification in low and high-risk that can be helpful for the clinical management of MDS patients.